The religious study gathering model of Maiyah Cahyo Sumebar as a form of inclusive communication in building religious harmony in Sukoharjo - Khoiriyah, Khoiriyah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
The religious study gathering (pengajian) of Maiyah Cahyo Sumebar in Sukoharjo represents a model of religious gathering that adopts an inclusive communication approach to promote interreligious harmony within a pluralistic society. Set against a socio-religious backdrop populated by diverse Islamic organizations such as NU, Muhammadiyah, LDII, MTA, alongside non-Muslim communities, this religious forum serves as an open spiritual dialogue space for all segments of society. This study aims to describe the Maiyah Cahyo Sumebar gathering model as a form of inclusive communication in strengthening religious harmony. Employing a descriptive qualitative method, data were collected through interviews, observations, and documentation. The findings reveal that this gathering model accommodates the principles of inclusivity through mutual respect, appreciation, cooperation, and interfaith solidarity. Mutual respect is reflected in the content of the sermons, which avoids triggering sectarian or theological conflicts. Collaboration involves residents, including non-Muslim figures, in organizing committees and event implementation. Social activities, such as charitable donations to the underprivileged, also play a significant role in fostering interfaith solidarity. This model embodies the principle of equality in socio-religious life, echoing the message of QS. Al-Hujurat (49:13), which encourages people to know one another amidst their differences. Therefore, Maiyah Cahyo Sumebar’s study gathering functions not only as a spiritual forum but also as a model of inclusive communication that nurtures interreligious harmony in a multicultural setting like Sukoharjo. ***** Pengajian Maiyah Cahyo Sumebar di Sukoharjo merupakan model pengajian yang mengusung pendekatan komunikasi inklusif dalam membangun kerukunan beragama di tengah masyarakat yang majemuk. Dengan latar sosial keagamaan yang dihuni oleh beragam organisasi masyarakat Islam seperti NU, Muhammadiyah, LDII, MTA, serta komunitas non-muslim, pengajian ini tampil sebagai ruang dialog spiritual yang terbuka bagi semua kalangan. Penelitian ini bertujuan untuk mendeskripsikan model Pengajian Maiyah Cahyo Sumebar sebagai wujud komunikasi inklusif dalam penguatan kerukunan umat beragama. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa model pengajian ini mengakomodasi prinsip inklusivitas melalui sikap saling menghormati, menghargai, bekerjasama, dan tolong-menolong antarkelompok agama. Sikap saling menghormati tampak dalam materi pengajian yang tidak memicu konflik antarmazhab atau keyakinan. Kerjasama melibatkan warga lokal, termasuk tokoh non-muslim, dalam pembentukan panitia dan penyelenggaraan kegiatan. Kegiatan sosial seperti santunan kepada fakir miskin juga menjadi bagian dari upaya memperkuat solidaritas lintas iman. Model pengajian ini mencerminkan prinsip kesetaraan dalam kehidupan sosial-keagamaan, sebagaimana semangat QS. Al-Hujurat (49:13), yang mendorong manusia untuk saling mengenal dalam perbedaan. Oleh karena itu, Pengajian Maiyah Cahyo Sumebar tidak hanya berfungsi sebagai ruang spiritual, melainkan juga sebagai model komunikasi inklusif dalam merawat kerukunan beragama di wilayah multikultural seperti Sukoharjo.